GUIDELINES FOR THE TRAINING OF TRAINER (TOT) MODEL: GROUP-BASED PSYCHOTHERAPEUTIC MODULES TRAINING IN PAKISTAN - Qamar, Tania; Ibrahim, Nabisah (Journal of Ayub Medical College Abbottabad, 2024)
Background. A detailed set of guidelines is needed for the Training of Trainers (TOT) model, which aims to include cultural awareness and values in group-based psychotherapeutic training. This will allow for the development and use of effective and culturally appropriate mental health care interventions in Pakistan. The current study aims to develop a TOT model with the goal of adding cultural values and sensitivity by training trainers and setting basic rules and guidelines that mental health professionals will follow as they are taught the group therapy modules, one step at a time. Methods. The TOT model for the step-by-step use of the group therapy module was developed in this study in several stages by using multiphase approach. Results. The findings reveal that this study developed a nine-step TOT model. Further explored was the relevance of these TOT programs for trainees to prepare them as literate trainers in group therapy interventions. In addition, the findings of the current study provided extensive knowledge of TOT guidelines and outlines and their further implications for psychotherapy training in Pakistan. The TOT model improves the skills and knowledge of trainers so they can continue to use the TOT model, which can then be used to teach others. It also helps find effective group-based psychotherapeutic interventions that can be used in Pakistan in the future. Conclusion. The results conclude that the guidelines for the TOT model emphasize how important it is to be culturally competent when conducting group therapy modules. These guidelines could be helpful in building up group-oriented modules among trainers who prepare or develop such training programs, which would ultimately be helpful for mental health professionals with varying cultural traditions.